2010
DOI: 10.1111/j.1567-1364.2010.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

The serine/threonine protein phosphatase Sit4p activates multidrug resistance in Saccharomyces cerevisiae

Abstract: Multidrug resistance in Saccharomyces cerevisiae is frequently associated with gain-of-function mutations in zinc finger-containing transcription factors Pdr1p and Pdr3p. These regulatory proteins activate the expression of several ATP-binding cassette transporter genes, leading to elevated drug resistance. Here, we report that loss of the type 2A-related serine/threonine protein phosphatase Sit4p renders yeast cells sensitive to cycloheximide, azoles, daunorubicin and rhodamine 6G. This effect is a consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Among these targets are several genes involved in SL biosynthesis such as IPT1, LCB2, SUR2 and LAC1 [31, 32]. In addition, Sit4p affects Pdr3p expression and SL biosynthesis [91]. Whether this effect is mediated via a Pdr3p mechanism is yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these targets are several genes involved in SL biosynthesis such as IPT1, LCB2, SUR2 and LAC1 [31, 32]. In addition, Sit4p affects Pdr3p expression and SL biosynthesis [91]. Whether this effect is mediated via a Pdr3p mechanism is yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both Pdr1p and Pdr3p appear important players in multidrug resistance as gain of function mutations in PDR1 and PDR3 increase expression of their target genes encoding multidrug efflux pumps [85]. Furthermore, PDR3 expression increases upon loss of the mitochondrial genome during the retrograde response and is regulated by both Pdr3p itself [86] and Sit4p [91]. …”
Section: The Retrograde Response Interacts With Sphingolipid Homeomentioning
confidence: 99%
“…Total protein lysates were prepared as in Miranda et al ., ;. Cells were grown in YPD at 30 °C to the indicated cell densities and harvested by centrifugation at 800 g , for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Disruption of the entire coding region of SIT4 was performed in a BY4741 background using one-step gene targeting with pFa6a-KAN-MX6 (Longtine et al, 1998). The oligonucleotides used are as previously described (Miranda et al, 2010). For the double deletion Dpdc5 Dsit4, a BY4741 Dsit4 background was used by exchanging the KAN (geneticin) marker used in the SIT4 deletion for a NAT (nourseothricin) marker (Hentges et al, 2005).…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…Four regulatory subunits of Sit4 has been identified, and they are named Sit4 association proteins (SAPs) and divided into two groups based on sequence similarity, the SAP4/SAP155 group and the SAP185/SAP190 group (Luke et al, 1996). Studies have shown that the SAPs have diverse functions, such as the regulation of cell growth, K + efflux, and drug resistance (Luke et al, 1996;Manlandro et al, 2005;Miranda et al, 2010). In C. albicans, Sit4 has been identified as the catalytic subunit of PP2A-like protein phosphatase, and deletion of SIT4 causes a significant reduction in growth rate, morphogenesis, and virulence in mice (Lee et al, 2004;Noble et al, 2010).…”
Section: Introductionmentioning
confidence: 99%